"Nos caminhos da psicologia capixaba": notas para a história da psicologia, da psiquiatria e da saúde pública no Estado do Espírito Santo - Lima, Milena Fiorim de (2005)
This study aimed at investiganting the insertion of the first psychologists in the public health services in the State of Espírito Santo (Brazil) and its historical circumstances, presenting a contribution to the History of Psychology, Psychiatry and Public Health. Several aspects of these historical events have been analyzed: the situation of local psychiatry with details of the type of treatment furnished by psychiatrists to patients at the Hospital Adauto Botelho and the Pronto Socorro Psiquiátrico of Cachoeiro de Itapemirim before the insertion of the first psychologists following the arrival of these professionals at the psychiatric institutions; the partnerships established between psychiatrists and psychologists following the arrival of these professionals at the psychiatric institutions; the treatment furnished by psychologists to patients of these institutions and the changes in the psychiatric institutions after the insertion of this new professional category, the psychologist. Two psychiatrists, three psychologists and an auxiliar nurse answered a semi-structured interview. Besides that, documents of the time supplied by the State Health Secretary and found in the Public Archives of Espírito Santo have been analyzed. The results indicate, among other points, that the insertion of the first psuchologists in the public health services in the Espírito Santo took place from 1976 on, in a local context full of criticism against the prevalent notion of madness and the therapeutics offered to those considered mentally ill and, even, taking into account the problem of social injustices. So, original actions were adopted at the time to face this situation.